Radioactivity in soil from the city of Kavadarci (Republic of Macedonia) and its environs - Dimovska, Snezana; Stafilov, Trajce; Sajn, Robert (Oxford University Press (OUP), 2012)
The activity concentrations and distribution of natural and anthropogenic radionuclides in soils from the city of Kavadarci, Republic of Macedonia, and its environs were investigated. The purpose of the study, the first of this kind in this region was to evaluate the environmental radioactivity and radiological health hazard, as well as to determine the connection between the concentration of natural radionuclides and the geology of the terrain. A total of 45 surface soil samples were collected from evenly distributed sampling sites. Gross alpha and gross beta activity measurements were made using a gas flow proportional counter, while the activity concentrations of gamma emitting radionuclides were measured using a high purity germanium detector. The average activity concentrations of ⁴⁰K, ²²⁶Ra, ²³²Th and ¹³⁷Cs were found to be 546±118, 38.8±14.6, 43.7±18.4 and 41.5±40 Bq kg⁻¹, respectively. The mean values of gross alpha and gross beta activities were 522±192 and 681±146 Bq kg⁻¹. The mean total absorbed dose rate in air calculated from the concentration of the natural radionuclides was 67.1±20.9 nGy h⁻¹, and the corresponding annual effective dose rate outdoors was 0.082±0.026 mSv y⁻¹. The results of the analysis show strong correlation between the abundance of the natural radionuclides in soils and their geological origin.